Non-canonical Estrogen Signaling in Endocrine Resistance - Ranganathan, Prathibha; Nadig, Namratha; Nambiar, Sughosha (Frontiers in Endocrinology, 2019)
Breast cancer is one of the leading causes of cancer related deaths in women worldwide. The disease is extremely heterogenous. A large percentage of the breast cancers are dependent on estrogen signaling and hence respond to endocrine therapies which essentially block the estrogen signaling. However, many of these tumors emerge as endocrine resistant tumors. Many mechanisms have been proposed to explain the emergence of endocrine resistance, which include mutations in the estrogen receptors, cross-talk with other signaling pathways, cancer stem cells etc. This review is focused on the role of non-canonical estrogen receptor signaling in endocrine resistance. Most of the therapeutics which are used currently are targeting the major receptor of estrogen namely ER-Last two decades has witnessed the discovery of alternate forms of ER-as well as other receptors for estrogen such as ERRgamma, GPER-1 as well as ER-which are activated not only by estrogen, but also by the therapeutic agents such as tamoxifen that are routinely used in treatment of breast cancer. However, when the alternate receptors are activated, they result in activation of membrane signaling which subsequently activates pathways such as MAPK and GPCR leading to cell-proliferation. This renders the anticipated anti-estrogenic effects of tamoxifen less effective or ineffective. Future research in this area has to focus on the alternate mechanisms and develop a combinatorial strategy, which can complement the existing therapeutics to get better outcome of endocrine therapies.